Strategi Komunikasi Pemasaran Brand Familias melalui Media Sosial Instagram dalam Meningkatkan Minat Beli Konsumen - Wara, Rafli Aditya; Fadillah, Dani (P3M Politeknik Negeri Media Kreatif, 2025)
An effective marketing communication strategy on social media, especially Instagram, is key to a brand's success. This research aims to see the potential of marketing communication strategies carried out by the Familias brand through the Instagram social media platform and assess their impact on consumer buying interest and gain a deeper understanding of how the Familias brand uses Instagram as a marketing platform and how these strategies affect consumer purchasing decisions. The theory in this research uses Integrated marketing communication (IMC) theory. The research method used is indirect observation with a descriptive qualitative approach. Data was collected through participant observation to observe interactions with Familias brand content on Instagram and Youtube. The research findings confirm that local brands are able to optimize social media as a means to increase exposure and reach potential target consumers more effectively. The digital marketing strategy carried out by the Familias brand has succeeded in increasing consumer buying interest in the products being marketed.